2018
DOI: 10.1111/izy.12187
|View full text |Cite
|
Sign up to set email alerts
|

Studying primate personality in zoos: implications for the management, welfare and conservation of great apes

Abstract: As we face the Anthropocene extinction, many species are threatened or becoming so, and great ape species are no exception (all are Endangered or Critically Endangered). As humans work to combat this trend, research on every aspect of the lives of animals is vital. One area of research that has the potential to be particularly useful is the study of personality. Zoological institutions offer a unique opportunity for research on personality in non-human primates, with knowledgeable staff, consistency in environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 93 publications
0
27
0
Order By: Relevance
“…Last but not least, studying the relationship between personality and measures like interest or motivation can have important implications for animal welfare. Given that individuals with different personality profiles may benefit from different types of cognitive enrichment ( Carere & Locurto, 2011 ), understanding individual differences in personality may be transferred to improving management and quality of life in animals under human control, thus having a positive impact on welfare and conservation ( Gartner & Weiss, 2018 ). In line with this, besides personality, future cognitive research involving captive animals should also consider including welfare indicators that can be monitored during experimental testing.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, studying the relationship between personality and measures like interest or motivation can have important implications for animal welfare. Given that individuals with different personality profiles may benefit from different types of cognitive enrichment ( Carere & Locurto, 2011 ), understanding individual differences in personality may be transferred to improving management and quality of life in animals under human control, thus having a positive impact on welfare and conservation ( Gartner & Weiss, 2018 ). In line with this, besides personality, future cognitive research involving captive animals should also consider including welfare indicators that can be monitored during experimental testing.…”
Section: Discussionmentioning
confidence: 99%
“…Growing research in animal personalities has demonstrated personality differences between animals (e.g. Gartner & Weiss, 2018) and these differences are likely to impact individual welfare in ways that a natural behaviour perspective, with its emphasis on species norms, cannot account for 3 . Even Webster, one of the original authors of the Five Freedoms account now thinks 'freedom of choice' would be a better behavioural criterion for capturing the important aspects of behaviour relative to welfare -the ability of an animal to choose those 2 See Swaisgood (2007) for a useful summary of theories about the relationship between behaviour and welfare in this sense 3 Thanks to an anonymous reviewer for this point.…”
Section: Alternative Criteriamentioning
confidence: 99%
“…Welfare assessment is becoming increasingly important in current day zoological and agricultural research [13,114,115,116]. In zoos, this issue is particularly vital to the increasing number of captive breeding programs, which aim to conserve natural behaviors amongst captive, threatened species whilst simultaneously trying to provide these animals with adjustment to a restricted environment where they may live their whole lives [14]. In farming, welfare considerations are increasing in response to growing consumer demand and intensification of livestock production, which simultaneously contributes to concern for the health and wellbeing of animals bred for their products.…”
Section: The Concept Of Stress Coping Styles and Its Relation To Amentioning
confidence: 99%
“…The study of individual differences is now wide spread across both ecology and psychology. The importance of considering individual differences in the study of behavior [1,2,3], cognition [4,5], development [6,7], stress responses [8,9,10], fitness and life history outcomes [11,12], and wellbeing [13,14,15] has been well established. Yet, the field of personality which has sprung up amidst this research is not short of critics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation